Investigation Into Magnetic Reconnection Formation on Propellant Ignition in Electrical Explosion - Zhang, Jiangbo; Liu, Wei; Xiao, Fei; Liang, Taixin; Zhao, Shusen (Frontiers in Physics, 2021)
Magnetic reconnection, in which magnetic lines break and reconnect to change their topology to a lower-energy state. This process can liberate stored magnetic field energy and accelerate particles during unsteady, explosive events. Here we report that the observations of the magnetic reconnection and kink instability of plasma jet in single wire electrical explosions and their effect on propellant ignition. The results showed that the initial velocity of plasma was 2000 m/s, and the velocity increased was 400 m/s when the magnetic reconnection occurred. The evaluated Alfvén velocity was 500 m/s, the Alfvén time was 20 μs, and the Lundquist number S=1.7×107. Based on these experimental results and model, the three-dimensional magnetic field topology and its evolution process was evaluated and presented. Further, the magnetic reconnection occurred when its curvature reached a specific value due to the elasticity of magnetic lines, and then the plasma jet was accelerated and exhausted. The plasma jet angle was 50° in experiment 1, and it was consistent with the calculated results. The resulting magnetic reconnection plays an important role in propellant ignition, which enhances the ignition ability of wire electrical explosion. Furthermore, the results represent a key step towards resolving one of the most important problems of plasma physics and can be used to improve the understanding of wire array explosion and propellant ignition.